The plastid outer envelope – a highly dynamic interface between plastid and cytoplasm - Breuers, Frederique; Braeutigam, Andrea; Weber, Andreas P. (Frontiers in Plant Science, 2011)
Plastids are the defining organelles of all photosynthetic eukaryotes. They are the site of photosynthesis and of a large number of other essential metabolic pathways, such as fatty acid and amino acid biosyntheses, sulfur and nitrogen assimilation, and aromatic and terpenoid compound production, to mention only a few examples. The metabolism of plastids is heavily intertwined and connected with that of the surrounding cytosol, thus causing massive traffic of metabolic precursors, intermediates, and products. Two layers of biological membranes that are called the inner (IE) and the outer (OE) plastid envelope membranes bound the plastids of Archaeplastida. While the IE is generally accepted as the osmo-regulatory barrier between cytosol and stroma, the OE was considered to represent an unspecific molecular sieve, permeable for molecules of up to 10 kDa. However, after the discovery of small substrate-specific pores in the OE, this view has come under scrutiny. In addition to controlling metabolic fluxes between plastid and cytosol, the OE is also crucial for protein import into the chloroplast. It contains the receptors and translocation channel of the TOC complex that is required for the canonical post-translational import of nuclear-encoded, plastid-targeted proteins. Further, the OE is a metabolically active compartment of the chloroplast, being involved in, e.g., fatty acid metabolism and membrane lipid production. Also, recent findings hint on the OE as a defense platform against several biotic and abiotic stress conditions, such as cold acclimation, freezing tolerance, and phosphate deprivation. Moreover, dynamic non-covalent interactions between the OE and the endomembrane system are thought to play important roles in lipid and non-canonical protein trafficking between plastid and endoplasmatic reticulum (ER). While proteomics and bioinformatics has provided us with comprehensive but still incomplete information on proteins localized in the plastid IE, the st